2020
DOI: 10.1111/bjh.16430
|View full text |Cite|
|
Sign up to set email alerts
|

Blood counts in adult and elderly individuals: defining the norms over eight decades of life

Abstract: The blood count is one of the most common tests used for health assessment. In elderly individuals, selection of a 'healthy' reference population for laboratory assessment is difficult due to the high prevalence of chronic morbidities, leading to uncertainty regarding appropriate reference intervals. In particular, age-specific lower haemoglobin reference limits to define anaemia are controversial. Here, we applied a data mining approach to a large dataset of 3 029 904 clinical routine samples to establish blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
3
14
1
Order By: Relevance
“…It is a physiological finding that the prevalence of asymptomatic and mild anaemia increases in apparently healthy elderly, which is also confirmed by other studies, 12‐14 suggesting that the decrease in haemoglobin levels might be a consequence of the normal ageing process. Similarly, Phillips et al show nutritional deficiency and age‐associated renal dysfunction are not the main reason for age‐related trends 15 .…”
Section: Discussionsupporting
confidence: 79%
“…It is a physiological finding that the prevalence of asymptomatic and mild anaemia increases in apparently healthy elderly, which is also confirmed by other studies, 12‐14 suggesting that the decrease in haemoglobin levels might be a consequence of the normal ageing process. Similarly, Phillips et al show nutritional deficiency and age‐associated renal dysfunction are not the main reason for age‐related trends 15 .…”
Section: Discussionsupporting
confidence: 79%
“…Older age alone contributes to anaemia with the evidence of low erythropoietin level in the blood even though the older persons did not have chronic illnesses 42,43 . Haemoglobin level among healthy older person is physiologically decreasing with increasing age, however the cut-off point among older men remained at 13g/dL 44 . Older person tends to develop undernutrition due to lack of food, feeding problems, inappropriate diet or malabsorption 30 .…”
Section: Discussionmentioning
confidence: 89%
“…It has been argued that these criteria may not be appropriate for the elderly population [ 5 ]. Studies conducted on healthy elderly individuals showed a decline in hemoglobin and red cell counts with increasing age in males [ 6 ]; it is therefore possible that what we are considering as anaemia in the elderly may in actual sense be the norm in this population. Studies performed on a larger data-base' with participants over 60 years of age are needed to develop a clearly defined diagnostic criteria of anaemia in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…It further classifies the anaemia severity into mild, moderate, and severe based on the hemoglobin levels [2]. Whilst this definition is being applied for all populations, different studies argue that the data used excluded individuals above 65 years of age [4][5][6]. Nevertheless, in adults aged 60 years and above, anaemia has notable adverse consequences of impaired functionality, cognition, increased hospital admissions, and increased morbidity and mortality [7,8].…”
Section: Introductionmentioning
confidence: 99%